Pengaruh Profitabilitas Dan Pertumbuhan Perusahaan Terhadap Struktur Modal Pt. Bumi Teknokultura Unggul Tbk - Yessyta Mardalena; Ustadus Sholihin; Zulfia Rahmawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims to determine the partial and simultaneous influence between the profitability ratio and the company's profit growth ratio on the capital structure of PT. Bumi Teknokultura Unggul Tbk Period 2014-2021. This research is a type of descriptive research with a quantitative approach. The data sources used are secondary data sources from the Indonesia Stock Exchange website. The sampling technique in this study used purposive sampling method. The results showed that the Profitability Ratio represented by the Return On Equity had a significant negative effect on the Capital Structure represented by the Debt to Equity Ratio at PT. Bumi Teknokultura Unggul Tbk in 2014-2021. Then the Company's Growth Ratio represented by Growth of Sales has a significant negative effect on the Capital Structure represented by the Debt to Equity Ratio at PT. Bumi Teknokultura Unggul Tbk in 2014-2021. And the Profitability Ratio and Growth ratio have a significant negative effect on the Capital Structure at PT. Bumi Teknokultura Unggul Tbk in 2014-2021.